Ethics and responsibility of a diagnostic psychologist at preschool - Mominova, Kh (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The psychologist is responsible for monitoring the interests of the subject, ensuring his psychological comfort at all stages of the psychodiagnostic examination, defined in the form of certain norms and rules of professional behavior. The basis of professional ethics is the recognition of the right of every person to the inviolability of the psyche, soul. The diagnostic psychologist must respect the dignity, human rights andfreedoms, religious and moral beliefs of the subject, take them into account when organizing and conducting research, and choose methodological tools. Discrimination on the basis of social origin, ethnicity, financial situation, sexual orientation, etc. Not allowed during psychological and diagnostic examination